Rural families and work context and problems - Bauer, Jean W.; Dolan, Elizabeth M.; SpringerLink (Online service). (New York Springer, 2011)
The recent economic downturn has been especially devastating in America's rural areas, where low wages, sporadic seasonal work, and manufacturing industries moving their plants out of the U.S. are widespread, and grocery stores and health care services may be miles away. Many families eligible for government programs are unaware of them. The transition from welfare to work is made more difficult by not only the fewer employment opportunities, and the limited access to transportation and child care which keeps many who want to work locked in a catch-22 of unemployment.  Rural Families and Work analyzes in context the issues and policies that have the greatest influence on rural employment. An overview of relevant theories provides a central starting point for discussion of work and its relationship to family and community well-being. Data from the Rural Families Speak project (including interview transcripts from study participants) illustrate the range of problems preventing rural families from finding and maintaining adequate employment. In addition, the book evaluates current proposals, pinpoints future directions for research and policy, and features discussion questions to help bring work-related issues into focus. Among the topics examined in detail:  The impact of TANF, EITC, and other aid programs. The challenges of child care for low-income rural mothers. Obstacles to employment: mental health problems and child health problems. The hunger-obesity paradox and other physical health issues. Social support and resource management among rural families. Food insecurity  between Latino and white populations. With its in-depth framework for understanding this complex subject, Rural Families and Work is a valuable text for family relations professors and students, and a solid reference for researchers studying social policy and the economics of the family.
Rural families and work overview / Jean W. Bauer, Elizabeth M. Dolan -- Theories for studying rural families and work / Jean W. Bauer, Elizabeth M. Dolan -- Rural does matter: understanding the rural context / Jean W. Bauer ... [et al.] -- Making rural employment work / Elizabeth M. Dolan, Jean W. Bauer, Mary Jo Katras -- Physical health, food security, and economic well-being: the rural perspective / Yoshie Sano, Leslie N. Richards -- Invisible barriers to employment: mental and behavioral health problems / Yoshie Sano, Leslie N. Richards, Jaerim Lee -- The challenge of child care for rural low-Income mothers / Susan K. Walker, Margaret M. Manoogian -- Resources as the key to rural employment / Carolyn L. Bird, Elizabeth M. Dolan, Sharon B. Seiling -- "I don?t know how we would make it": social support in rural low-income families / Sharon B. Seiling, Margaret M. Manoogian, Seohee Son -- The earned income tax credit: an Incentive to rural employment / Sheila Mammen, Frances C. Lawrence, Jaerim Lee -- Applications for the RFS findings: programs and future research / Jean W. Bauer, Elizabeth M. Dolan, Bonnie Braun -- Policy issues and applications: rural concerns / Elizabeth M. Dolan, Jean W. Bauer, Bonnie Braun.
Electronic reproduction.
Keywords: Rural families -- Economic aspects -- United States; Electronic books